Automatic Generation Control of Two Equal Areas with Traditional Controllers - Ankita Rani; Harinder Singh; Krishan Arora (Institute of Advanced Engineering and Science, 2016)
Automatic generation control (AGC) is major issue in power system whose main purpose is to maintain the frequency and tie line power flow during normal period in an interconnected system. . Thus, It is the responsibility of the Power system engineers to ensure that adequate power is delivered to the load reliably and economically so that nominal condition will be re-established The main focus is to maintain the value of frequency in its prescribed limit. We use renewable source which are important as well as non renewable sources at the level of extinct. As renewable alone cannot reliable then we use interconnection of both for making the system reliable and more efficient.This research paper is devoted to explore the interconnection of the automatic generation control of hydro power system and wind system. The wind system is comprised with governor dead band, generation rate constraint and turbine dynamics where as the hydro system is comprised with generation rate constraint. The traditional PI controller does not have adequate control performance with the consideration of nonlinearities and turbine dynamics. To overcome this drawback, PID controllers helps in solving optimization problems by exploitation of random search. It will provide the system security also for maintain the frequency in prescribed limit with the help of simulation.